2012
DOI: 10.4081/ijas.2012.e78
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propolis product on digestibility and ruminal parameters in buffaloes consuming a forage-based diet

Abstract: This study evaluated the Propolis product (LLOS) effects on feed intake, dry matter (DM) and nutrients total digestibility, rumen characteristics and microbial efficiency in buffaloes fed a roughage based diet (70% Cynodon spp hay and 30% concentrate). Using a 4¥4 latin square design, four crossbred buffalo (Murrah x Jafarabadi) steers (519.0±13.0 kg body weight - BW), were fed four treatments with three LLOS concentrations: Control (no LLOS), LLOS B3+ (0.272 mg/g flavonoid chrysin equivalents), LLOS C1 (0.092… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…The same study (Morsy et al, 2015) confirmed the improvement in the ruminal degradation of organic matter with propolis. Similarly, increases in total SCFA and butyrate concentrations were observed for crossbred buffalo steers fed different doses of Brazilian propolis, and this effect was associated with the increase in total tract DM digestibility (Costa et al, 2012). Increased SCFA concentrations in the rumen and DM digestibility were also reported by Stradiotti Júnior et al (2004) in Holstein steers fed a diet containing 65% forage and 35% supplemented with propolis in the concentrate.…”
Section: Propolis On Ruminal Microbial Fermentation and Digestionsupporting
confidence: 62%
See 1 more Smart Citation
“…The same study (Morsy et al, 2015) confirmed the improvement in the ruminal degradation of organic matter with propolis. Similarly, increases in total SCFA and butyrate concentrations were observed for crossbred buffalo steers fed different doses of Brazilian propolis, and this effect was associated with the increase in total tract DM digestibility (Costa et al, 2012). Increased SCFA concentrations in the rumen and DM digestibility were also reported by Stradiotti Júnior et al (2004) in Holstein steers fed a diet containing 65% forage and 35% supplemented with propolis in the concentrate.…”
Section: Propolis On Ruminal Microbial Fermentation and Digestionsupporting
confidence: 62%
“…However, the authors did not report any information about the place of propolis collection or chemical composition. Costa et al (2012) observed an increase of the DM digestibility without reduction in ammonia production in buffalo steers. All these findings may refer that different propolis extracts may enhance the ruminal nutrient degradability while reduce the deamination of amino acids and/or growth rate of amino acid-fermenting bacteria.…”
Section: Propolis On Ruminal Microbial Fermentation and Digestionmentioning
confidence: 81%
“…Despite the higher antioxidant value than those of moringa products, the addition of raw propolis did not drastically modulate the ruminal fermentation and the gas production parameters in the present experiment. Some researchers explored the effects of the propolis extract [14,21,45,46] or propolis phenols [42] and consistently documented higher butyrate production. Data from earlier studies suggest that the polyphenolic compounds of propolis, for instance, caffeic acid [47], might have played a role because it supports the growth of gut butyrate-producing bacteria [48], which might have replaced the population of other bacteria, such as propolis which also possess microbial inhibition properties [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bee propolis has been recognized as a natural alternative feed additive to antibiotics in ruminant diets [54]. Compared to ionophores (e.g., monensin), different propolis sources can reduce CH 4 production while improving the organic matter digestibility and total SCFAs in vitro and in vivo [53,57]. Morsy et al [58] reported that CH 4 reduction caused by propolis supplementation is accompanied by increasing urinary allantoin, total purine derivatives, and enhancements of individual and total SCFAs.…”
Section: Propolismentioning
confidence: 99%